Determinants of climate change adaptation strategies and its impact on the net farm income of rice farmers in south-west Nigeria. (June 2020) - Ojo, T.O.; Baiyegunhi, L.J.S.
Highlights: Adaptation strategies to climate change. A multistage sampling technique was used to select cross-sectional data from 360 smallholder rice farmers. A Multivariate probit and Endogenous switching regression model. Investment in education is essential as a panacea for improving adoption of climate change adaptation strategies. Abstract: A multivariate probit (MVP) model was used to analyse the determinants of strategies adopted for adapting to climate change in a sample of smallholder rice farmers in south-west Nigeria. An efficient endogenous switching regression model (ESRM) was used to estimate the impact of climate change adaptation strategy on the net income of rice farmers. The MVP results show that the socio-economic factors, the institutional factors, and locational variables of some households statistically influenced the choice of climate change adaptation strategies employed. Complementarities among all the adaptation strategies used by the farmers were revealed by the positive pair-wise correlation matrix of the MVP model. The study also indicated that farmers affected by prolonged drought and incidences of flood were more likely to adopt adaptation strategies on their farmlands. The ESRM treatment effect indicated that the average net income per rice farm of those who adopted the strategies was significantly higher than that of those who did not. Thus, the government, stakeholders, and donor agencies must provide capacity-building innovations related to agricultural extension systems and climate change education through information and communication technologies. This investment in education is essential for development and would encourage farmers to adopt appropriate climate change adaptation strategies.